Net present value analysis of an automated grain aeration system technology on stored corn - Popelka, Paul (Kansas State University, 2015)
The purpose of this thesis is to analyze whether the use of automated aeration systems for reducing moisture in corn during storage provides sufficient net present value for Nebraska corn farmers. The objective is to examine if an automated aeration system provides sufficient energy savings, marketing opportunities and reduced drying costs before corn delivery to an elevator. On-the-farm corn storage has steadily increased and harvesting corn before the moisture has achieved the desired targets cost farmers in drying charges and shrink. Farmers are interested in whether automated aeration systems can remove enough moisture from grain, without over-drying the bin, without spending a large amount of time determining when to run their grain bin aeration fans. Data for this project were obtained from four privately owned 60,000 bushel grain bins outfitted with the IntelliAir™ BinManager™ automated aeration system. Moisture samples were taken from each of the trucks hauling grain to the bin and again after removal of the corn after the automated system had ran for 9 months. Energy usage, drying charges, and shrink were calculated for the initial corn moisture averages and the moisture at the time of removal. Each bin was examined using Net Present Value (NPV) analysis to determine whether the energy savings were enough to offset the initial installation cost and annual expenses of the project. After the NPV was estimated for each of the bins, a sensitivity analysis of how corn price changes and no aeration required would affect the NPV analysis. Finally, an analysis of the total costs savings of a continuously ran aeration system was compared to the automated aeration system. The conclusion of the NPV analysis was that adding an automated aeration system would be profitable under most scenarios. More studies are needed to determine the profitability of automated aeration systems in different regions, moisture inputs, and bin sizes.
Keywords: Automatic Aeration System; Investment Analysis; Grain Drying; Nebraska Corn Storage; Grain Storage; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)